2017
DOI: 10.1016/j.ccell.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

SPOP Mutation Drives Prostate Tumorigenesis In Vivo through Coordinate Regulation of PI3K/mTOR and AR Signaling

Abstract: Summary Recurrent point mutations in SPOP define a distinct molecular subclass of prostate cancer. Here, we describe a mouse model showing that mutant SPOP drives prostate tumorigenesis in vivo. Conditional expression of mutant SPOP in the prostate dramatically altered phenotypes in the setting of Pten loss, with early neoplastic lesions (high-grade prostatic intraepithelial neoplasia) with striking nuclear atypia, and invasive poorly differentiated carcinoma. In mouse prostate organoids, mutant SPOP drove inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
180
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(196 citation statements)
references
References 51 publications
(106 reference statements)
16
180
0
Order By: Relevance
“…Consistent with these findings, SPOP mutations were previously implicated in androgen signaling because both AR and AR coactivators undergo deregulation in the presence of SPOP mutations [8486]. AR signaling was more frequently altered in metastatic samples, most often by amplifications or mutations of AR , which were essentially absent in localized prostatic cancers [87].…”
Section: Molecular Characteristics Of Prostatic Cancersupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with these findings, SPOP mutations were previously implicated in androgen signaling because both AR and AR coactivators undergo deregulation in the presence of SPOP mutations [8486]. AR signaling was more frequently altered in metastatic samples, most often by amplifications or mutations of AR , which were essentially absent in localized prostatic cancers [87].…”
Section: Molecular Characteristics Of Prostatic Cancersupporting
confidence: 62%
“…A recent study demonstrated that CHD1 is a putative synthetic-essential gene in PTEN -deficient cancers, and CHD1 depletion profoundly and specifically suppresses cell proliferation in PTEN -deficient prostate cancers [118]. Another recent study showed that SPOP mutations activate both PIK3/MTOR and AR signaling pathways, effectively uncoupling the normal negative-feedback mechanism between these two pathways [86]. …”
Section: Molecular Characteristics Of Prostatic Cancermentioning
confidence: 99%
“…We observed MAPK driver mutations in HRAS (p.Q61K, 2%) and BRAF (p.G469A, 1%). Putative dominant negative SPOP mutations were present in 5% of cases (Barbieri et al, 2012; Blattner et al, 2017). ETS gene family activations were mutually exclusive with activating alterations in the RAS/MAPK pathway members ( P = 0.01, Fisher’s exact test) and with inactivation of SPOP and CHD1 (Barbieri et al, 2012; Burkhardt et al, 2013; Huang et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 10% of prostate cancer patients harbor SPOP mutations (Barbieri et al , ). In this subtype of prostate cancers, both AKT and AR signaling are aberrantly activated (An et al , ; Geng et al , ; Blattner et al , ; Zhang et al , ). Currently, strategies for effectively treating this unique subclass of patients remain to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…The gene encoding SPOP is the most frequently mutated gene in human primary prostate cancers (Barbieri et al , ; Cancer Genome Atlas Research Network, ). Functional studies show that ectopic expression of the most frequent SPOP‐mutant F133V in human prostatic cells or knock‐in in the mouse prostate results in aberrant activation of AR and AKT‐mTORC1 signaling (An et al , , ; Geng et al , ; Blattner et al , ; Zhang et al , ). Most importantly, the Cancer Genome Atlas (TCGA) data demonstrate that SPOP‐mutated prostate cancers exhibit the highest AR activity among all molecular subtypes of prostate cancer examined (Cancer Genome Atlas Research Network, ).…”
Section: Introductionmentioning
confidence: 99%